Pengaruh Konten Youtube Fiersa Besari “Atap Negeri” terhadap Sikap Mahasiswa Pecinta Alam dalam Melestarikan Lingkungan - Milda Irnadianis Ipada; Alfi Satria; Wiena Safitri (CV. Ulil Albab Corp, 2023)
In the millennial era, Youtube has become a promising field of work, as can be seen in one of the content creators named Fiersa Besari, besides being a writer and musician, Fiersa is also a Youtube content creator with 3.2 million subscribers. On her personal channel, Fiersa takes on the topic of nature and creates a grand adventure through the project